The Imperial Gaze: Bingham and Machu Picchu - Flores Espinoza, Javier (2019)
In Peru, the discovery of Machu Picchu has proved to be a bone of contention ever since Hiram Bingham first climbed the mountain and reached the Inca settlement. The dispute between Yale University and the Peruvian government over the possession of the archaeological artefacts which Bingham «temporarily» removed from Peru only soured the discussion further. The centennial of Bingham’s «discovery» saw both parties finally reach a settlement, as well as the publication of several books which either study these archaeological materials or explore Bingham’s life and work. And yet Bingham still remains an issue in Peru, the agreement notwithstanding. This love-hate relationship with the American explorer will only be solved once Peru comes to terms with its past, for what is at stake is not so much Bingham, but how Peru conceives and understands its history.